Measuring the Impact of Pesticide Use, Labor Availability, and Agricultural Technology on Vegetable Farming Efficiency in Central Java - Fatma Sarie; Iwan Harsono (West Science Interdisciplinary Studies, 2024)
This research investigates the intricate dynamics influencing vegetable farming efficiency in Central Java, focusing on the interplay of Agricultural Technology, Labor Availability, and Pesticide Use. A quantitative approach employing Structural Equation Modeling (SEM) with Partial Least Squares (PLS) is employed, analyzing data from a diverse sample of 171 vegetable farms. The results reveal significant positive relationships between Agricultural Technology, Labor Availability, and Pesticide Use with Vegetable Farming Efficiency. The study sheds light on the nuanced associations among these factors, highlighting the potential benefits of technological adoption and skilled labor while emphasizing the need for sustainable and responsible pesticide use. Subgroup analyses based on farm size and geographical location provide insights into tailored interventions for different contexts. The findings contribute to the discourse on sustainable agricultural development, providing actionable insights for policymakers, farmers, and stakeholders in Central Java.